Mental Resilience In Humanitarian Aid Providers From Non Psychiatrist Perspective - Razali, Zul Azlin; Md Zin, Ahmad Rostam bin; Omar, Mohd Rahman Bin (International Journal of Human and Health Sciences (IJHHS), 2025)
Mental resilience is essential for humanitarian aid workers to maintain their wellbeing while addressing crises. This resilience encompasses adapting, coping with, and recovering from stress and difficulties. Aid workers frequently encounter demanding situations, emotional fatigue, and ethical challenges. They can boost their resilience through self-care strategies, including regular exercise, fostering social connections, and engaging in mindfulness practices. Furthermore, organisations can promote resilience by offering stress management training, facilitating open communication, and developing supportive workplace environments. Peer support initiatives can also be beneficial, enabling aid workers to exchange experiences and coping methods. Identifying burnout signs and applying preventive strategies is crucial for helping aid providers remain effective. Ultimately, mental resilience enhances their effectiveness and sustainability in assisting. Mental resilience is vital for humanitarian aid providers’ operational success and longevity. Aid workers can bolster their resilience by emphasising self-care, nurturing supportive relationships, and securing organisational support. This improves their wellbeing and enhances their capacity to deliver aid with effectiveness and compassion in some of the most challenging conditions globally. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S19